Organizational Capacity of Cianjur Main Rice Seeds Development - Mohammad Iqbal; Ryta Mirna; Elisa Susanti (Jurnal Manajemen Pelayanan Publik, 2021)
The increasing number of people causes the need for food to increase so that the need for seed development so that food availability can be fulfilled this can be seen through the organizational capacity, especially in Cianjur, West Java, where this location is one of the areas in Indonesia that is used in efforts to develop parental rice seeds. The purpose of this research was to determine and analyze how the organizational capacity of developing Cianjur rice seeds was. The theory used in this research is Horton's theory of organizational capacity. This research uses qualitative research methods and is described descriptively. The results showed that the organizational capacity of the Cianjur Parental rice seed development organization still had problems such as limited resources, technology and budget, causing the program to be implemented could not be used optimally.